Paris: The Musical Kaleidoscope 1870-1925 - Brody, Elaine (New York Braziller, 1987)
In our day when serious new music has often found its audience only among specially prepared little groups of avant-garde enthusiasts, it is worthwhile to be reminded how different things were a century ago. In 19th-Century Italy strong nationalist passions were aroused by the very name of Verdi (its letters standing in cipher for Victor Emmanuel re d'Italia-- Victor Emmanuel king of Italy), and Wagner imagined audiences for his operas modeled on the presence of whole urban populations in the Greek theater. (Even though people complained then as now that his works were overlong and boring, the passion he inspired did recall his ancient ideals.)Nowhere was music's powerful everyday presence more marked than in Paris, where the new opera house occupied as important a place in social and cultural life as it did in the city's geography, where modernist ballet drew all the arts into partnership around a musical center, and where Symbolist poets and painters during the fin de siecle took music as the exemplary art.Elaine Brody, a professor of music at New York University, has undertaken to bring this period in French musical history to life in her new book. She ranges over a richly varied scene, moving from the legacy to Berlioz to the influence of Wagner, the fascination for exotic and oriental themes, the place of music in the series of Great Expositions that were so characteristic of the "century of progress," and the proliferation of new musical locales. There are separate treatments of Spaniards, Russians and Americans in Paris and program notes for outstanding composers and works of the era. Readers will find much fascinating detail, presented in a clear and often lively style.
Keywords: 19th Century (1801-1900); 20th Century (1901-2000); Music history; Paris (France)